Expert Consensus on Clinical Practice of Burn Units in Shanghai During the COVID-19 Epidemic - Ma, Bing (J Burn Care Res, 2021)
In response to coronavirus disease 2019 (COVID-19), the Shanghai Burn Clinical Quality Control Center organized experts to formulate and implement a set of rapid, simple, and effective prevention and control measures, and there have not been any cases of health care professionals or inpatients in burn units suspected or confirmed with COVID-19. This article elaborates on the specific measures in burn units in response to the epidemic, including the implementation of standardized procedures, remote consultations, strengthened follow-up, exchange of experience, and popular science, among others. We share experience from Shanghai to benefit related disciplines in other countries and regions.